Developing the characteristic spirit of publicly managed schools in a more secular and pluralist Ireland. Issue 3 (4th May 2018) - O'Flaherty, J.; McCormack, O.; Gleeson, J.; O'Reilly, B.; O'Grady, E.; Kenny, N.
Abstract: This discussion paper considers the identification and definition of the 'characteristic spirit' of publicly managed schools in the Republic of Ireland. Some international approaches to values in publicly funded schools are introduced along with relevant contextual aspects of Irish education including the cultural diversity and secularisation of modern Irish society. The Irish Education Act (1998) gives ultimate responsibility for school values and 'characteristic spirit' to the school 'patron', a role legally separate from that of school ownership and school management. The underlying values of privately managed faith-based schools are well established. However, the 'characteristic spirit' of publicly managed Education and Training Board schools remains largely undeveloped. Appropriate responses to this challenge are identified and discussed.